Decreased level of plasma nesfatin-1 in rats exposed to cell phone radiation is correlated with thyroid dysfunction, oxidative stress, and apoptosis. (2nd November 2022) - Hussien, Noha I.; Mousa, Ayman M.; Shoman, Abeer A.
Abstract: Context: Exposure to Electomagnetic radiation fields of cell phones causes thyroid dysfunction and a previous study revealed that nesfatin-1 may affect functions of the thyroid gland. Objective: To study the role of nesfatin-1 on functions of rat's thyroid gland exposed to EMRF. Materials and methods: Thirty adult male rats were divided equally into 3 groups as group I, group II and group III. The experiment extended for 30 days then the plasma nesfatin-1 level, thyroid functions, and thyroid tissue oxidative stress were assessed. Also; histological and immunohistochemical study studies were done to evaluate structural and apoptotic changes of the thyroid gland. Results: There was a significant decrease in plasma nesfatin-1 level and thyroid functions with an increase in oxidative stress and apoptosis. Interestingly, there was a correlation between nesfatin-1 level and markers of thyroid function, oxidative stress and apoptosis. Conclusion: Nesfatin-1 plays a role in thyroid dysfunctions of rats exposed to mobile phone radiation.